+0  
 
+1
252
2
avatar+956 

 

A bit stuck here, any help?

 May 2, 2018
 #1
avatar+98197 
+2

Remember that    a(x1, y1)   - b(x2, y2 ) =   ( ax1 - bx2, ay1  - by2 )

 

a(3,4)  - b(2,4)   =  (8,10)

 

So we have that

 

3a  - 2b  = 8      and

4a  - 4b  = 10

 

Multiply the first equation by - 2  all the way through

 

-6a  + 4b  =  -16     

4a  -   4b   =  10        add these

 

-2a   =  -6     divide both sides by  -2

a  = 3

 

And using   3a  - 2b  = 8  to  find b, we have that

 

3(3)  - 2b  = 8

9  - 2b  = 8 

-2b  = -1

b  = 1/2

 

 

cool cool cool

 May 2, 2018
edited by CPhill  May 2, 2018
 #2
avatar+1355 
+6

b = 1/2

 May 2, 2018

33 Online Users

avatar
avatar
avatar
avatar
avatar
avatar